Barriers on Using Social Media As Learning Tools Among Korean Pre-service Social Studies Teachers - Kang, Woonsun; Choi, Jaewoo (International Journal of Engineering and Technology, 2018)
This study aims to identify underlying types of deterrents on using social media as learning tools among Korean pre-service social studies teachers and to analyze whether gender and age are predictive of membership in types of deterrents. In order to achieve this goal, this research was conducted at Daegu University, Korea. For the purpose of this study, 207 social studies pre-service teachers were selected as sample, and responses were analyzed using latent class analysis (LCA) and multinominal logistic regression. We conducted analysis using PROC LCA for SAS environment. Study results are as follows. 1) the respondents were grouped into five latent classes: the technical barriers(12%), the situational and dispositional barriers(48%), the severe barriers(11%), the institutional barriers(23%), and the semi-economical barriers(6%). 2) Both gender (p<.001) and age(p<.001) were predictors of latent class membership.Â